(untitled) (Research, Society and Development, 2022)
This study aims to review the main effects of the performance order of resistance exercises on cardiovascular response in strength training (ST) sessions. To do so, a search was carried out in PubMed, BIREME, and Google Scholar databases using as descriptors: ’order’, ’resistance training order’, ’resistance exercise order’, ’blood pressure’ ’hypotension’, ’effect hypotensive’, ’post-exercise hypotension’ and ’cardiovascular responses’. After applying the inclusion/exclusion criteria, six studies were considered in this review. The results suggest that ST can be considered as a non-pharmacological therapeutic option against arterial hypertension. Although the alternate exercise sequence and the sequence that progresses from multi-joint exercises towards single-joint ones present a longer duration of the hypotensive effect in hypertensive individuals, literature needs more studies that investigate the influence of different exercise orders in the hypertensive audience for further conclusions on the subject.